AUTOMATED PROCESS CONTROL SYSTEM OF MOBILE CRUSHING AND SCREENING PLANT - Ostroukh, Andrey; Surkova, Nataliya; Varlamov, Oleg; Chernenky, Valery; Baldin, Alexander (Journal of Applied Engineering Science, 2018)
The article research the problem of automating the mobile crushing and screening plant as a complex multi-level system. The analysis of the characteristics of the technological equipment and individual aggregates of the mobile crushing and screening plant is performed.A software for automated cone crusher control system, that allows to integrate a set of interconnected technological units in the control of one hardware, controller and human-machine interface on the touch panel in the operator station.Proposed human-machine interface based on a set of technical, informational, mathematical and software tools for controlling the mobile cone crusher, which ensures effi cient operation of the technological control object as a whole.In accordance with the proposed concept, a complex automated system should provide an optimal level of automation for information collection and processing to form control signals and transfer them without loss and distortion to actuators in order to achieve effi cient operation of the technological line for the crushing and screening plant.
Keywords: Human-Machine Interface (HMI); Mnemonic scheme; Cone crusher; Jaw crusher; Crushing and screening plant; Automated process control system (APCS); Automation processes